Early 21st century cyclone climatology : a 3D perspective. Basic characterization - Lakkis, Susan Gabriela (2021)
Fil: Lakkis, Susan Gabriela. Pontificia Universidad Católica Argentina. Facultad de Ciencias Agrarias; Argentina